Effect of exercise training on swimming performance, survival under predation and hypoxia tolerance in an endangered fish species in China. Issue 2 (4th March 2019) - Zhou, Long-Yan; Yan, Xiang-Yue; Li, Xiu-Ming; Fu, Xiang; Xia, Ji-Gang; Fu, Shi-Jian
ABSTRACT: Poor swimming performance and low hypoxia tolerance have been suggested as the main reasons for the dramatic decrease in the wild population of Chinese sucker. The present study aimed to investigate the potential for exercise training to enhance swimming performance and hypoxia tolerance in this fish species targeted for stocking enhancement. Fish were exercise trained (force to swim against a flow) once daily, twice daily or not exercise trained for 20 d and then detrained for 10 d (a period of nontraining). Training showed no significant effect on anaerobic swimming performance.. The fish from both training groups showed lower hypoxia tolerance and a lower survival rate under predation. Thus, the present study suggested thatexercise training showed little effect or even a negative effect on physiological function in Chinese sucker, and the forced training might not be the proper protocol to apply for improving the stocking enhancement of Chinese sucker..